Investigation of Fattening Performance, Slaughter, Carcass, and Some Meat Quality Characteristics of Imported Simmental, Charolaise, and Belgian Blue × Holstein F1 Bulls - Necmettin Ünal; Mustafa Polat; Akın Yakan (Veterinary Medicine and Science)
ABSTRACT This research was carried out to examine the fattening performance, slaughter, carcass, and some meat quality characteristics under intensive fattening conditions of Simmental, Charolaise, and Belgian Blue × Holstein F1 (BB×H F1) bullocks imported from Europe to Türkiye. The animal material of the study consisted of 13 Simmental, 14 Charolaise, and 15 Belgian Blue × Holstein F1 (BB×H F1) bullocks, in a total of 42 heads. The fattening period of the Simmental, Charolaise, and BB×H F1 bullocks was started at 11 months of age with a live weight of 405–434 kg and finished at 19 months of age with a live weight of 648–742 kg. While Charolais had better values than other genotypes in terms of daily live weight gain and FCR, Simmentals had the highest carcass‐meat ratio. The meat quality traits of longissimus thoracic muscle ascertained at 24th hours after slaughter in the genotypes were obtained among 5.54–5.65 for pH and 13.72–16.45% for water holding capacity; 18.37–26.28% for cooking loss. It was determined that the fattening performances of imported Simmental, Charolaise, and BB×H F1 bullocks under intensive fattening conditions were acceptable, and the best in Charolaise bullocks compared with the other genotypes. While the ratios of the valuable cuts in the whole carcass, and selected meat quality characteristics were the lowest in Charolaise, it was determined that the ratios of various bones in the whole carcass were higher in the Simmental bullock compared with the other genotypes.